ISLAMIC GENDER EDUCATION AND WOMEN’S ROLES IN RELIGIOUS TRADITIONS: A CASE STUDY OF THE BAYAN COMMUNITY IN NORTH LOMBOK - Fadilah, Husni; Rapiko, Rapiko; Yahuda, M; Nugroho, Aris Dwi (Sekolah Tinggi Agama Islam Al Hidayah, 2026)
This study examines Islamic gender education in the traditional village of Bayan, North Lombok, a community characterized by strong religious and customary traditions. Despite Islamic teachings that emphasize justice and equality, gender disparities persist in various social and religious domains. This research aims to analyze how Islamic gender education is implemented and how the interaction between Islamic values and local customs shapes women’s roles within an indigenous Muslim community. Using a qualitative case study approach, data were collected through in-depth interviews, participant observation, and document analysis, and analyzed thematically. The findings reveal a gradual transformation in women’s roles from relatively passive participation to more active engagement in religious lectures, informal religious education, and customary activities. While informal institutions provide more equitable access for girls, formal religious leadership remains predominantly male-dominated. Support from families, religious leaders, and customary authorities strengthens women’s positions, although certain traditional practices continue to require contextual reinterpretation. This study contributes to the limited scholarship on Islamic gender education in indigenous contexts by demonstrating how religious principles and local traditions can be constructively negotiated to promote gender equality and support sustainable development goals.